Hubungan antara paritas dengan persalinan letak sungsang - Lidia Widia (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: The purpose of this study was to determine the relationshipbetween parity with the layout of Breech Birth on RSUD dr. H. AndiAbdurrahman Noor Kabupaten Tanah Bumbu. This research methodis analytic survey with cross sectional design. The population in thisstudy were all women who registered in the Delivery Room on RSUDdr. H. Andi Abdurrahman Noor Kabupaten Tanah Bumbu with asample of 510 respondents. The sampling technique used is totalsampling and testing data using chi-square test.The results showedrespondents who have breech deliveries of 210 respondents (41.2%)and normal delivery 300 respondents (58.8%). Of Chi-square testobtained There is a significant relationship between parity with breechdeliveries by value ñ = 0.000. The conclusion of this study therelationship between parity chest with breech deliveries in the DeliveryRoom RSUD dr. H. Andi Abdurrahman Noor Kabupaten TanahBumbu. Suggestions are expected for health workers to providecounseling to pregnant mothers and young checkups on a regularbasis in order to avoid breech.